Przegląd metod badawczych wykorzystywanych w badaniach pisma ręcznego w Polsce - Skubisz-Ślusarczyk, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The purpose of this paper is to present the process of devising and shaping the methods for handwriting research. The approach discussed in this presentation comprises various threads, as it covers the divisions based on different criteria which — in consequence — differ in their assumed aims, research process, and the obtained results. The type of the examined object is undoubtedly some sort of a parameter for the presented methods. Certain methods are aimed at examining short and long texts, while others are focused on examining signatures. One can also refer to a group of the so-called universal methods which are applied both to examine handwriting and signatures.This publication is addressed primarily to students, as it is a teaching aid during the forensic, criminal or civil procedure courses, but also to practitioners who — for professional purposes — appoint handwriting experts, and who require knowledge regarding handwriting research.
Keywords: pismo ręczne; metody badania pisma ręcznego; ekspertyza pisma ręcznego; długie teksty; krótkie teksty; podpisy